Application of Non-Standard Test Tasks in Teaching the Subject of “Lower Amu Darya Economic District” - Abdinazarova Xidoyatxon Oripovna; Abdinazarov Bunyodjon Khaliqnazarovich (Genius Journals, 2023)
The article is devoted to the use of non-standard test tasks in geography classes. In particular, non-standard test tasks developed to determine the extent to which students have mastered this topic in teaching the topic “Lower Amudarya Economic Region” are mentioned
Keywords: test; standard test; non-standard test; integrative test